2015
DOI: 10.1177/0956462415589044
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal douching and association with sexually transmitted infections among female sex workers in a prefecture of Yunnan Province, China

Abstract: Vaginal douching is a common practice and has been hypothesised to increase a woman's risk for human of contracting HIV and sexually transmitted infections (STIs). Our objective was to assess the prevalence of douching and its association with STIs, genital symptoms and HIV/STI knowledge among female sex workers (FSWs). We conducted a cross-sectional study of 837 FSWs with interviews and laboratory tests for HIV/STIs in a prefecture of Yunnan Province in southern China. Vaginal douching was reported by 84% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…Ekpenyong et al, reported a prevalence of 80% among young adult women in Nigeria. Furthermore, our prevalence rate is lower than the 84% reported among sex workers in Yunnam Province in China [21]; the 72% among women attending reproductive health clinic in Dar es Salaam in Tazania [19]. However, the reported prevalence in this study is higher than the 46% reported among black women at risk in Southern United States [6].…”
Section: Discussioncontrasting
confidence: 67%
“…Ekpenyong et al, reported a prevalence of 80% among young adult women in Nigeria. Furthermore, our prevalence rate is lower than the 84% reported among sex workers in Yunnam Province in China [21]; the 72% among women attending reproductive health clinic in Dar es Salaam in Tazania [19]. However, the reported prevalence in this study is higher than the 46% reported among black women at risk in Southern United States [6].…”
Section: Discussioncontrasting
confidence: 67%
“…35 The negative impact that routine douching can have on women’s reproductive health and vulnerability to HIV/AIDS and STIs has also been studied. 36 Our study found a strong association of RD prior to RAI with syphilis.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, frequent cleaning of one’s genitals and bathing have been associated with a high prevalence of STIs. Although, STIs are mostly caused by pathogens via unsafe and unprotected sexual behavior with multiple sexual partners or disloyal partners, many studies have demonstrated that genital hygiene practices also correlate with higher risks of STIs [35,36,37]. Inappropriate cleaning methods, such as vaginal touching, use of feminine wipes and alkaline lotion for genital and reproductive tract inevitably increase the chances of infection.…”
Section: Discussionmentioning
confidence: 99%